Can't understand how this works?Watch this thread
The revsion guide gave the answer as y+5=-1/4(x+2) or y=-1/4x-11/2
I got the y+5=-1/4(x+2) but can't understand how it could become y=-1/4x-11/2? Am I just being really dumb?
I'll attach a picture of the question in the revision guide, the answer in the revision guide, and my working out in case that can help any. Thanks!
(It's question 1, and sorry the working out is messy)
The first one just rearranges to give the second? You've done the difficult bit lol x
if you expand the right hand side you get y+5=-1/4x-1/2 then if you want y on its own you have to take away five, to make it easier to understand I will take away 10/2 which is 5. so y=-1/4x-10/2-1/2 which is y=-1/4x-11/2